Aerospace series. Heat resisting alloy FE-PA2601. Softened and cold worked. Bar for forged fasteners. D ≤ 50 mm. 1 100 MPa ≤ Rm ≤ 1 300 MPa. (23rd January 2020) - British Standards Institution,
No abstract available